Effect of Preirradiation Fluoride Treatment on the Physical Properties of Dentin. (17th March 2022) - Mante, Francis K.; Kim, Aaron; Truong, Kristi N.; Mittal, Kriti; Alapati, Spoorthi; Hagan, Sarah; Deng, Jie
Abstract : Objective . To determine the effects of preirradiation fluoride treatments on the Knoop hardness of dentin. Materials and Methods . Human posterior teeth mounted into acrylic resin molds were polished with silicon carbide (SiC) abrasives and 3-micron diamond paste. The Knoop hardness of dentin was measured with a Leco hardness instrument. The teeth were divided into groups of ten teeth per group as follows: no treatment (control), treatment with silver diamine fluoride (SDF), MI varnish (MI), and cavity shield (CS). The teeth were exposed to 2 Gy of daily radiation for six weeks using an X-Rad 320ix biological irradiator. Hardness was measured weekly, before, during, and after irradiation. The teeth were stored in artificial saliva at 37 o C between radiation treatments. Results . In preirradiation dentin, a Knoop hardness value of 58.8 (14.1) KHN was obtained. Treatment with SDF significantly increased KHN before irradiation. Immediately after radiation treatment, hardness was significantly reduced in all experimental groups. Postirradiation fluoride treatments increased the hardness of dentin to varying degrees. Conclusions . Preirradiation fluoride treatment does not provide protection from decreases in the hardness of dentin. Treatment of teeth with fluoride formulations after radiation progressively restores the hardness of dentin to different degrees.